PENGARUH DIGITAL LITERACY DAN GUIDANCE KEAGAMAAN TERHADAP EMPLOYABILITY SKILLS MAHASISWA DENGAN LEARNING ENGAGEMENT SEBAGAI VARIABEL MEDIASI - Hidayati, Nurul; Abidin, Munirul (STKIP Pesisir Selatan, 2026)
This study aims to analyze the effect of digital literacy and religious guidance on students' employability skills with learning engagement as a mediating variable. The study uses a quantitative approach with an explanatory research design. The research sample consisted of 52 active students in at least their third semester, selected through purposive sampling. Data were collected using a five-point Likert scale questionnaire and analyzed using Partial Least Squares-based Structural Equation Modeling (SEM-PLS) with the help of SmartPLS software. The results of the analysis show that all research instruments meet the criteria for validity and reliability. Digital literacy has a positive and significant effect on students' learning engagement and employability skills, while religious guidance has a positive and significant effect on learning engagement, but does not have a significant direct effect on employability skills. In addition, learning engagement has a positive and significant effect on students' employability skills. The mediation test shows that learning engagement does not significantly mediate the effect of digital literacy on employability skills, but shows a tendency to be a partial mediator in the relationship between religious guidance and employability skills.